Profile of Students’ Character in the Reading to Learn (R2L) Model in Improving Scientific Literacy Skills - Arief Muttaqiin; Aisyah Salsabila Dwi Ananda; Putri Aulia; Pakhrur Razi; Yusefarina Yusefarina; Lahara Yanuarsi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the description of the character of students during learning with the Reading to Learn (R2L) Model in order to improve their scientific literacy skills. This learning was carried out for 3 meetings on dynamic electricity material. During the study, observations were made by two observers using an observation sheet containing the student's character. Aspects of student character observed in this study were curiosity, adaptability, social behavior, and initiative. The students observed consisted of four classes. The number of students involved was 64 students (n=64). Based on observations, the highest character that emerges from students during learning is the character of socio-cultural behavior (52.95%), while the lowest character is curiosity (44.44%).